2019
DOI: 10.1016/j.actbio.2018.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclasts in bone regeneration under type 2 diabetes mellitus

Abstract: Diabetes mellitus (DM) affects hundreds of million people worldwide and the impaired bone healing is an important DM-related complication. Understanding how DM affects the activities of osteoclasts and the underlying mechanisms is crucial to the development of effective approaches for accelerating bone healing in DM condition. To date, however, the influence of DM on osteoclasts remains obscure and controversial. In this study, we established a type 2 DM (T2DM) alveolar bone defect model, which closely simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 39 publications
1
46
1
Order By: Relevance
“…Arachidonic acid metabolism: the altered arachidonic acid metabolism and the increased ratio of thromboxane A2 to prostacyclin, which favored an enhanced thrombotic state, may play a role in the accelerated vascular disease of diabetes mellitus [84]. Osteoclast differentiation: it was reported that T2DM could inhibit osteoclastogenesis and osteoclast activity, and delay the degradation of matrix during the alveolar bone regeneration in T2DM rats [85].…”
Section: Experiments Resultsmentioning
confidence: 99%
“…Arachidonic acid metabolism: the altered arachidonic acid metabolism and the increased ratio of thromboxane A2 to prostacyclin, which favored an enhanced thrombotic state, may play a role in the accelerated vascular disease of diabetes mellitus [84]. Osteoclast differentiation: it was reported that T2DM could inhibit osteoclastogenesis and osteoclast activity, and delay the degradation of matrix during the alveolar bone regeneration in T2DM rats [85].…”
Section: Experiments Resultsmentioning
confidence: 99%
“…Many proteolytic enzymes such as MMP-2, MMP-9, or cathepsin-K were involved in bone remodeling process [32], and MMPs were key degrading enzyme expressed in either physiological [33] or pathological conditions including osteoarthritis [34], and osteoporosis [35]. The concentration of MMP-2 increased around two times, and MMP-9 increased around ten times under bone formation and disease environment [36][37][38]. In this MMP-9 enriched condition, we observed all PBS, MeGC, and Hep-MeGC groups suffered decrement of BMP-2 bioactivity ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many proteolytic enzymes such as MMP-2, MMP-9, or cathepsin-K were involved in bone remodeling process [32], and MMPs were key degrading enzyme expressed in either physiological [33] or pathological conditions including osteoarthritis [34], and osteoporosis [35]. The concentration of MMP-2 increased around two times, and MMP-9 increased around ten times under bone formation and disease environment [36][37][38]. In this MMP-9 enriched condition, we observed all PBS, MeGC, and Hep-MeGC groups suffered decrement of BMP-2 bioactivity (Figure 2a).…”
Section: Discussionmentioning
confidence: 99%